2010
DOI: 10.1103/physrevb.82.033403
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal pits created by single highly charged ions inBaF2single crystals

Abstract: In various insulators, the impact of individual slow highly charged ions ͑eV-keV͒ creates surface nanostructures, whose size depends on the deposited potential energy. Here we report on the damage created on a cleaved BaF 2 ͑111͒ surface by irradiation with 4.5ϫ q keV highly charged xenon ions from a roomtemperature electron-beam ion trap. Up to charge states q = 36, no surface topographic changes on the BaF 2 surface are observed by scanning force microscopy. The hidden stored damage, however, can be made vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…8(b) and (e)) [77][78][79]. In these cases each individual ion impact develops into a pyramidal etch pit, as can be concluded from a comparison of the areal density of observed etch pits with the applied ion fluence.…”
Section: Slow Highly Charged Ionsmentioning
confidence: 96%
See 1 more Smart Citation
“…8(b) and (e)) [77][78][79]. In these cases each individual ion impact develops into a pyramidal etch pit, as can be concluded from a comparison of the areal density of observed etch pits with the applied ion fluence.…”
Section: Slow Highly Charged Ionsmentioning
confidence: 96%
“…In these cases each individual ion impact develops into a pyramidal etch pit, as can be concluded from a comparison of the areal density of observed etch pits with the applied ion fluence. A size analysis reveals the significance of the deposited potential energy in the creation of these pits [77,79]. Although the defects are not mobile enough to directly lead to desorption, the ion's impact region is structurally weakened by the potential energy deposition and therefore susceptible to chemical etching.…”
Section: Slow Highly Charged Ionsmentioning
confidence: 99%
“…3) to remain qualitatively valid. For BaF 2 (111) and KBr (001) for example, we have previously observed only the A and B phases [22,31]. The phase diagram predicts that by further increasing the potential energy of the HCI we should be able to reach region C, i.e.…”
mentioning
confidence: 94%
“…The defect mediated desorption mechanism is less probable in CaF 2 , since color center recombination below the surface is much more likely [27] agglomerates [28,29]. The material in the vicinity of the impact region is not ablated but structurally weakened and forms the nucleus of an etchable defect subsequently removed by a suitable etchant [22]. The synergistic effect induced by the accompanying kinetic energy originates from kinetically induced defects created in the collision cascade which enhance the trapping of the color centers created by potential energy [30] and therefore increases defect agglomeration.…”
mentioning
confidence: 99%
“…Therefore, the interaction of HCI with surfaces may not be described in terms of an equilibrium charge state dependent stopping force. Furthermore, due to the localization of the energy deposition slow HCI can be used as an efficient tool for surface nano-structuring [13][14][15][16][17][18][19][20][21][22][23][24] and tuning of the electrical properties of materials [25], as well as a probe for surface energy deposition processes [26,27]. Recently, it has been shown that slow HCI can create pores in 1 nm thick carbon nanomembranes (CNM) [28,29] mainly by deposition of their potential energy [30].…”
mentioning
confidence: 99%